Poor Science; Poorly Trained Scientists; Poor Policies: Major Deterrents to the War on Cancer (Journal of Cancer Research Updates, 2018)
Although the availability of funding has been described as the major limitation on advances in cancer, the progress in the war on cancer has been deterred mainly by poor science, poorly trained scientists, and poor NIH policies. This is the result of NIH policies of its extreme focus on molecular biology (genomics, molecular genetics, molecular biology) identification of the molecular factors and pathways; which are required for the acceptability of treatment and preventive protocols. As such, this has influenced virtually all agencies that provide grants for medical research to adopt the NIH policies. This has impacted the funding of the research as well as the focus of the training of scientists. Directors of NCI Dr. Varmus (also Nobel Prize awardee) and Dr. Zerhouni had addressed this issue; and they rejected the necessity of molecular biology studies and information. NIH should return to the holistic physiological/pathophysiological approach to studies of cancer issues. This would provide the best approach for winning the war on cancer.